National Comparative Audit of Blood Transfusion: report on the 2014 audit of patient information and consent. Issue 4 (28th November 2017) - Booth, C.; Grant‐Casey, J.; Lowe, D.; Court, E. L.; Allard, S.
SUMMARY: Objectives: The aim of this study was to assess current practices around obtaining consent for blood transfusion and provision of patient information in hospitals across the UK and identify areas for improvement. Background: Recommendations from the Advisory Committee on the Safety of Blood, Tissues and Organs (SaBTO) (2011) state that valid consent should be obtained for blood transfusion and documented in clinical records. A standardised source of information should be available to patients. Practices in relation to this have historically been inconsistent. Methods: The consent process was studied in hospitals across the UK over a 3‐month period in 2014 by means of an audit of case notes and simultaneous surveys of patients and staff. Results: In total, 2784 transfusion episodes were reviewed across 164 hospital sites. 85% of sites had a policy on consent for transfusion. Consent was documented in 43% of case notes. 68% of patients recalled being given information on benefits of transfusion, 38% on risks and 8% on alternatives and 28% reported receiving an information leaflet. In total, 85% of staff stated they had explained the reason for transfusion, but only 65% had documented this. 41% of staff had received training specifically on transfusion consent in the last 2 years. Conclusions: There is a need to improve clinical practice in obtaining valid consent for transfusion in line with existing national guidelines and local Trust policies, with emphasis on documentation within clinical records. Provision of patient information is an area particularly highlighted for action, and transfusion training for clinicians should be strengthened.